2016
DOI: 10.5296/ijhrs.v6i1.9199
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Job Satisfaction in Higher Education Sector: Empirical Insights from Malaysia

Abstract: Job satisfaction is one of the most important topics in the field of management and it has received a noteworthy attention from both scholars as well as business practitioners. This is because employee job satisfaction is the main predictor of organizational success and long term performance. This paper examines the impact of four factors namely employee engagement, employee motivation, work environment, and organizational learning on job satisfaction in higher education sector. The data were collected using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 29 publications
0
15
1
Order By: Relevance
“…Employee engagement is how an employee is energized (Shuck & Reio, 2013), absorbed, dedicated, enthusiastic, and shows vigor towards his/her job (Macey & Schneider, 2008).Engaged employees are deeply involved, interested in their work, and they have high levels of job satisfaction (Biswas & Bhatnagar, 2013), where as disengaged employees are disconnected from work rationally, emotionally, and motivationally (Sunny & Joshua, 2014). Studies have shown a positive relationship between employee engagement and job satisfaction (Hanaysha, 2016;Imam & Shafique,2014;Kamalanabhan, Prakash Sai & Mayuri, 2009).The present study hypothesizes the following: H3: A positive relationship exists between employee engagement and job satisfaction.…”
Section: Relationship Between Employee Engagement and Job Satisfactionmentioning
confidence: 69%
“…Employee engagement is how an employee is energized (Shuck & Reio, 2013), absorbed, dedicated, enthusiastic, and shows vigor towards his/her job (Macey & Schneider, 2008).Engaged employees are deeply involved, interested in their work, and they have high levels of job satisfaction (Biswas & Bhatnagar, 2013), where as disengaged employees are disconnected from work rationally, emotionally, and motivationally (Sunny & Joshua, 2014). Studies have shown a positive relationship between employee engagement and job satisfaction (Hanaysha, 2016;Imam & Shafique,2014;Kamalanabhan, Prakash Sai & Mayuri, 2009).The present study hypothesizes the following: H3: A positive relationship exists between employee engagement and job satisfaction.…”
Section: Relationship Between Employee Engagement and Job Satisfactionmentioning
confidence: 69%
“…The teaching work satisfaction-and its motivation-not only depends on salary conditions (Machado et al 2011). The work environment has an equal impact on it (Hanaysha 2016), with everything related to the students being the main source of motivation and demotivation, as Kızıltepe (2008) defines as the vocational factor of teaching. In fact, the lack of social relationships with the students is one of the reasons why the professors wish to return to the teaching activity (Souto Santos et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a study conducted by Hanaysha (2016) also found that organizational learning has significantly affect job satisfaction. Thus, organizational learning signifies the capability of an organization in increasing the skills and knowledge of its workers to safeguard better productivity and efficiency at workplace.…”
Section: International Journal Of Human Resource Studiesmentioning
confidence: 95%
“…Moreover, the attention given towards researching job satisfaction has shown the importance of this topic. Thus, to be successful, organizations need to make sure that the workers are satisfied with their jobs (Hanaysha, 2016). As discussed above, job satisfaction is an important factor applied to evaluate organizational effectiveness (Khan, Anjam, Faiz & Khan, 2020).…”
Section: International Journal Of Human Resource Studiesmentioning
confidence: 99%
See 1 more Smart Citation